EFFECT OF ELECTRICAL STIMULATION ON pH OF BEEF - M. Sunil; E. Nanu; R. Padmanabha Iyer (Journal of Veterinary and Animal Sciences, 1995)
The effect of electrical stipulation on changes in pH of meat stored at ambient and refrigeration temperatures showed that electrical stimulation has brought down the pH and the pH of ES samples was significantly lower than flat liar the C samples at 0, 1, 2, 4 and 8 h of storage both at ambient and refrigerated temperatures. At 24 h of storage, the pH values of ES and C samples were not significantly different. Electrical stipulation followed by storage at ambient temperature helped to bring down the pH of meat below 6.00nt a shorter tine.